Evaluation of perception of social network from the technological acceptance model in Mexican online Psychology students (Praxis Educativa, 2022)
The objective was to evaluate and describe the perception of social networks from the Technological Acceptance Model to describe the attitude, perceived usefulness, ease of use, trust, and perceived risk of social networks used by online psychology students. The study was non-experimental, transactional, with correlational scope. It was a non-probabilistic sample of 74 students from different regions of Mexico with an average age of 35 years, of which 56 were women. The Technological Acceptance Instrument (TAM) adapted to virtual social networks was used. The results show that Facebook is the most widely used social network. The Risk and Trust scales showed moderate means, the rest showed high means. It was found that at an older age the perception of Ease of use decreases. Women showed a higher perception of Risk and Facebook users showed a lower perception of Utility.
Keywords: social media; Internet; perception; attitude; Communication technology